2021
DOI: 10.3390/ani11041001
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Circulating Immune Complexes in Horses with Severe Equine Asthma

Abstract: Non-invasive diagnostic biomarkers of equine asthma syndrome (EAS) from blood or urine are sought. The aim of this study was to assess the absorbance of circulating immune complexes (CICs) during the exacerbation, remission, and treatment of an asthma episode and assess the potential usefulness of CIC levels in the diagnosis and monitoring of the disease. The control group, asthma group, and treated asthma group each contained six horses. Following an initial examination and group classification, the horses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In the current study, no association between serum NGAL and EA diagnosis was demonstrated, nor between serum NGLA and with BAL NGAL concentration or BAL neutrophils. These results are in line with previous EA research and blood biomarkers have not shown reliable differences between EA cases and healthy horses 35–39 . While our results do not indicate a potential benefit for serum NGAL as a marker of EA, due to the limited sample size, with only 66 serum samples, future studies should be performed to confirm this.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, no association between serum NGAL and EA diagnosis was demonstrated, nor between serum NGLA and with BAL NGAL concentration or BAL neutrophils. These results are in line with previous EA research and blood biomarkers have not shown reliable differences between EA cases and healthy horses 35–39 . While our results do not indicate a potential benefit for serum NGAL as a marker of EA, due to the limited sample size, with only 66 serum samples, future studies should be performed to confirm this.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with previous EA research and blood biomarkers have not shown reliable differences between EA cases and healthy horses. [35][36][37][38][39] While our results do not indicate a potential benefit for serum NGAL as a marker of EA, due to the limited sample size, with only 66 serum samples, future studies should be performed to confirm this. In humans, a possible relationship between airway remodelling caused by airway neutrophilia and NGAL has been proposed, 5,40 and NGAL is found to increase in response to chronic inflammation 41 but this has not yet been investigated in horses.…”
Section: Concentration Of Ngal Inmentioning
confidence: 80%
“…According to the general properties of equine IgG3 and IgG5, these mechanisms could be immune complex formation and Fcg receptor binding to support respiratory burst and complement fixation (the latter by IgG3) (43). These pathological mechanisms have only been discussed for equine asthma (2,19,20). Similarly, mouse models of human allergic asthma point to the exacerbation of airway inflammation and hyperreactivity by allergen-specific IgG and immune complexes activating innate immune cells through FcgRs (21).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies analyzed IgG (6,13,14) and found increased Asp f 7-or Asp f 8-specific IgG in serum (6,13) or Asp extract-binding IgG in BALF (15). Other than these, IgG analyses concerning SEA are sparse even though they could be informative: i) allergen-specific IgG isotypes are are usually induced in addition to IgE (16)(17)(18), and ii) IgG-dependent mechanisms like type III hypersensitivities and involvement of immune complex formation have been suggested as a pathological mechanism of equine asthma (2,19,20). Similarly, mouse models of human asthma indicated such mechanisms and increased allergenspecific IgG was associated with asthma in humans (21).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these genes are responsible for the regulation of T-cells (IL-27) or associated with inducing allergies by inhalation (IL-7R) in human asthma development [ 19 ]. A number of reports on clinical aspects of severe equine asthma are available [ 20 , 21 ], including the search for non-invasive blood or urine biomarkers [ 22 ]. Equine asthma is well known as an animal model of human asthma [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%